Learning about water through the African catchment game : the refinement of a role playing simulation game - Fraenkel, Linda Anne (Rhodes University, Faculty of Science, Department of Geography, 2010)
This research has undertaken two key mandates. One was to develop modifications to the African Catchment Game (ACG), a role playing simulation game, in order to simulate rainfall and water management processes representative of the southern African context. The other was to understand what, if any, learning associated with water management issues had taken place as a result of playing the ACG. The modification process took the form of an action research process. The initial modifications were trialed with South African students as part of their undergraduate Geography course offered at Rhodes University, South Africa. Subsequent modifications were implemented over a five month period with three diverse participant groups, namely Finnish, American and South African participants. An interpretive research orientation was employed in order to analyse both the qualitative and quantitative data that was generated. Pre- and Post-Game Questionnaires were used in order to identify the learning and understanding which the participants constructed as a result of playing the ACG. The Chi-Square Test was also applied to each of the pre- and post- questions to establish statistical significance. Subsequent analysis of these questions identified and traced patters and trends associated with learning and understanding across the three game runs. This research study draws on social constructivism and experiential learning as the dominant education theory that underpins it. Results revealed that for all three game runs learning took place. Participants identified dominant themes and environmental dimensions both before and after playing the ACG. The analysis of these responses indicated a deeper awareness of water as a contributing factor for sustainable economic development while the game runs enabled the researcher to adjust the water availability within each game run until rainfall and water management processes representative of a southern African context were successfully simulated in the last game run.
Keywords: Water -- South Africa -- Management -- Simulation methods; Water -- Management -- Study and teaching; Rain and rainfall -- South Africa -- Simulation methods; Simulation games in education Role playing